EDITORIAL - The Language Teaching Journal (2024)
The Scientific Journal Kronos: The Language Teaching Journal, presents to our readers Vol ume 5, Number 1 in its digital version, and at the same time put to your consideration several approaches related to the teaching and learning of languages from different per spectives, which will allow the researcher to obverse with a critical view the diverse real ities in the construction of knowledge.